2010
DOI: 10.3233/ch-2010-1342
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Acoustic Radiation Force Impulse Imaging to transient elastography to assess liver stiffness in healthy volunteers with and without valsalva manoeuvre

Abstract: Purpose: Acoustic Radiation Force Impulse Imaging (ARFI) is a new ultrasound elastography technology (Siemens ACUSON S2000 Virtual Touch TM Tissue Quantification), which is integrated in conventional ultrasound equipment. In preliminary studies, ARFI sheer wave speed (SWS) in liver tissue correlated well with transient elastography (TE) values and liver fibrosis stages.Materials and methods: Sixty-eight healthy male and female volunteers were measured with ARFI with two ultrasound tranducers, three measuring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 16 publications
6
45
0
Order By: Relevance
“…Other elastographic methods were not sensitive to the Valsalva maneuver or yielded mixed results. [18][19][20] The contrast to previously published research exploring the impact of the Valsalva maneuver on liver stiffness is most likely related to a number of factors, including the following: (1) time-harmonic elastographic mechanical excitation exploits a lower dynamic range than acoustic radiation force impulse or other transient-based elastographic measurements; (2) time-harmonic elastography can examine major portions of the right liver along profiles of approximately 14 cm in length; and (3) We used short breath-holding intervals of no longer than 3 seconds for our measurements. Breathing-related flow alterations have been demonstrated to be important for other elastographic methods as well.…”
Section: Discussionmentioning
confidence: 99%
“…Other elastographic methods were not sensitive to the Valsalva maneuver or yielded mixed results. [18][19][20] The contrast to previously published research exploring the impact of the Valsalva maneuver on liver stiffness is most likely related to a number of factors, including the following: (1) time-harmonic elastographic mechanical excitation exploits a lower dynamic range than acoustic radiation force impulse or other transient-based elastographic measurements; (2) time-harmonic elastography can examine major portions of the right liver along profiles of approximately 14 cm in length; and (3) We used short breath-holding intervals of no longer than 3 seconds for our measurements. Breathing-related flow alterations have been demonstrated to be important for other elastographic methods as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, others showed that respiratory status (e. g., apnea versus free-breathing) did not influence LSM [8]. Valsalva maneuver did not influence the values [53]. It has been suggested that a breath hold for a few seconds during quiet breathing may lead to optimal results [11,12].…”
Section: Respirationmentioning
confidence: 96%
“…By measuring during continuous speech or while crying, movement of the diaphragm is minimized. In literature a thereby produced Valsalva has no significant effect on the ARFI elastrography value [23].…”
mentioning
confidence: 88%